PENINGKATAN KINERJA GURU MELALUI SUPERVISI EDUKATIF SEMESTER I SD NEGERI DOMBO 1 KECAMATAN SAYUNG KABUPATEN DEMAK TAHUN PELAJARAN 2021/2022 - REJO REJO (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2021)
This study aims to 1) Improve Teacher Performance at SD Negeri Dombo 1 through educational supervision. 2) Describe the steps of collaborative educational supervisionperiodically in preparing learning implementation plans, implementing learning, assessing learning achievement, carrying out follow-up assessments of student achievement that can improve teacher performance. This performance improvement is carried out through periodic collaborative educational supervision.This action research was conducted on 16 teachers of SD Negeri Dombo 1, Sayung District, Demak Regency. The action research was carried out from September 2021 to November 2021. The research design used is an action research design (reserch) whose flow is: making an action plan, implementing the action, and reflecting on the implementation of the action. The results of these reflections are used as guidelines for making decisions to continue or stop the research. The research was carried out in a spiral in cycles until the second cycle. The research data are in the form of observation notes, field notes, planning documentation and supervision results. The main data collection instrument is the researcher, while the supporting instruments are observation and documentation guidelines. Data analysis was carried out using qualitative and quantitative techniques.The results showed that the teacher's performance increased after the action in the form of direct educative supervision was carried out from cycle I to cycle II. These improvements include improvements in preparing lesson plans, implementing learning, assessing learning achievement, carrying out follow-up assessments of student achievement Based on the results of educative supervision in cycle I and cycle II, teacher performance increased, namely in cycle I, teacher performance in preparing learning plans for cycle I reached 76%, while in cycle II it was 91%. The teacher's performance in implementing the learning cycle I reached 71% while the second cycle reached 89%. Teacher performance in assessing learning achievement in the first cycle reached 70% while the second cycle was 90%. Teacher performance in carrying out follow-up assessments of student achievement in the first cycle reached 54% while the second cycle was 84%. Thus, the average cycle II action was already above 75%. Based on the results of the action research, it can be concluded that the teacher's performance increases in preparing lesson plans, implementing learning, assessing learning achievement, carrying out follow-up assessments of student achievement. For this reason, researchers suggest that schools carry out educational supervision. ABSTRAKPenelitian ini bertujuan ingin Meningkatakan Kinerja Guru SD Negei Dombo 1 melalui supervisi edukatif. Mendeskripsikan langkah-langkah supervisi edukatif kolaboratif secara periodik dalam menyusun Rencana Pelaksanaan pembelajaran, melaksanakan pembelajaran, menilai prestasi belajar, melaksanakan tindak lanjut penilaian prestasi belajar siswa yang dapat meningkatkan kinerja guru. Peningkatan kinerja ini melalui supervisi edukatif kolaboratif secara periodik. Penelitian tindakan Sekolah ini dilakukan terhadap guru SD Negeri Dombo 1, Kecamatan Sayung Kabupaten Demak yang berjumlah 16 orang. Penelitian tindakan dilaksanakan mulai bulan September 2021 sampai dengan November 2021. Rancangan penelitian yang digunakan adalah rancangan penelitian tindakan (reserch) yang alurnya: membuat rencana tindakan, melaksankan tindakan, dan refleksi pelaksanaan tindakan. Hasil refleksi tersebut digunakan sebagai pedoman untuk pengambilan keputusan melanjutkan atau menghentikan penelitian. Penelitian dilakukan secara spiral dalam siklus-siklus sampai siklus kedua. Data penelitian berupa catatan hasil pengamatan, catatan lapangan, dokumentasi perencanaan dan hasil supervisi. Instrumen pengumpul data utama adalah peneliti, sedangkan instrument penunjangnya adalah pedoman observasi, dokumentasi. Analisis data dilakukan dengan teknik kualitatif dan kuantitatif. Hasil penelitian menunjukkan bahwa kinerja guru meningkat setelah dilakukan tindakan yang berupa supervisi edukatif secara langsung dari siklus I ke siklus II. Peningkatan tersebut meliputi peningkatan dalam menyusun rencana pembelajaran, melaksanakan pembelajaran, menilai prestasi belajar, melaksanakan tindak lanjut penilaian prestasi belajar siswa. Berdasarkan hasil penelitian tindakan tersebut dapat disimpulkan bahwa kinerja guru meningkat dalam menyusun rencana pembelajaran, melaksanakan pembelajaran, menilai prestasi belajar, melaksanakan tindak lanjut penilaian prestasi belajar siswa. Untuk itu, peneliti menyarankan agar di sekolah-sekolah melaksanakan supervisi edukatif.